Seed quality evaluation in the collection of Cyamopsis tetragonoloba after long-term storage under uncontrolled conditions - N. V. Rakovskaya; O. N. Zabegayeva; E. A. Dzyubenko (Труды по прикладной ботанике, генетике и селекции)
Background. Guar or clusterbean (Cyamopsis tetragonoloba (L.) Taub.) is an annual leguminous plant cultivated for feed, food and industrial purposes. Its seed endosperm is used to extract guar gum, so the guar genetic resources stored in the VIR collection are of strategic importance for the import substitution policy in Russia in the context of their prospective introduction into cultivation in the country’s southern areas. Most of the guar accessions had been preserved by VIR for 40 years or more, so the task was to assess their germination rates and restore their viability. In the process of screening, seed quality parameters of the accessions were examined and analyzed.Materials and methods. VIR’s collection of C. tetragonoloba, initiated by N. I. Vavilov, now contains 111 accessions. Percentage seed viability, germination energy and seed hardness were evaluated in the Long-Term Storage Laboratory for 50 accessions reproduced in 2018 and for 263 older reproductions of 89 guar accessions. In total, 313 seed samples reproduced across 18 different years were analyzed. Statistica 10 software was used to perform a single-factor analysis of variance and find out how germination energy, seed viability and seed hardness correlated with the age of seeds, mean monthly temperature and mean rainfall during the growing season.Results and discussion. After more than 40 years of storage, the guar accessions did not entirely lost their viability under laboratory and field conditions. Very high positive correlations were found for their percentage viability and germination energy with the mean monthly temperature in the year of reproduction. A weak positive correlation was observed between seed hardness and the year of reproduction. Correlations between seed viability and rainfall during the growing season were weak, with a weak negative correlation between seed hardness and rainfall. The viability level of 30-year-old seeds was 50%, so guar may be regarded as belonging to the group of macrobiotic plants.